2010
DOI: 10.1002/ceat.200900297
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline Flow Behavior of Water‐in‐Oil Emulsions with and without a Polymeric Additive in the Aqueous Phase

Abstract: New experimental results are presented on the pipeline flow behavior of water-inoil (W/O) emulsions with and without a polymeric additive in the aqueous phase. The emulsions were prepared from three different oils of different viscosities (2.5 mPa s for EDM-244, 6 mPa s for EDM-Monarch, and 5.4 mPa s for Shell Pella, at 25°C). The W/O emulsions prepared from EDM-244 and EDM-Monarch oils (without any polymeric additive in the dispersed aqueous phase) exhibited drag reduction behavior in turbulent flow. The turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 27 publications
1
13
0
3
Order By: Relevance
“…It was reported that since the measured turbulent pressure drop was lower than that calculated from Blasius equation, drag reduction was claimed (Cengel et al (1962), Pal (1987, Pal (1993), and Omer and Pal (2010)) and such drag reduction is enhanced as: the dispersed phase fraction increases (Pal (1987) and Pal (1993)); the pipe diameter decreases (Pal (1993) and Masalova et al (2003)) and as the viscosity of oil continuous decreases (Omer and Pal (2010)). Moreover, drag reduction is a function of emulsion type (Pal 1993) and pipe material (Angeli and Hewitt (1998)).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…It was reported that since the measured turbulent pressure drop was lower than that calculated from Blasius equation, drag reduction was claimed (Cengel et al (1962), Pal (1987, Pal (1993), and Omer and Pal (2010)) and such drag reduction is enhanced as: the dispersed phase fraction increases (Pal (1987) and Pal (1993)); the pipe diameter decreases (Pal (1993) and Masalova et al (2003)) and as the viscosity of oil continuous decreases (Omer and Pal (2010)). Moreover, drag reduction is a function of emulsion type (Pal 1993) and pipe material (Angeli and Hewitt (1998)).…”
Section: Introductionmentioning
confidence: 91%
“…Droplets stretching and elongation, in turbulent regime, is proposed as a mechanism of the reported drag reduction of studied unstable emulsions (Pal (2007)). Furthermore, phase inversion of unstable emulsions was also reported (Pal (1993) little or no drag reduction was addressed for surfactant stabilized water-in-oil emulsions (Pal (1993) and Omer and Pal (2010)). In addition, (Pal (1993) and Omer and Pal (2010)) reported that as the dispersed phase fraction increased, phase inversion and an increase in emulsion effective viscosities were reported.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The stability of water-in-crude oil emulsion results from the tendency for dispersed water droplets to resist coalescence (Chan and Tao 2005). The droplet size distribution is an important emulsion characteristic influencing a range of emulsion properties including its rheology (Aichele et al 2016;Omer and Pal 2010;Pal 1993Pal , 2007Pal , 2011. Hence, measurement of these W/O emulsion droplet sizes as a function of AA enables a better understanding of the impact of their addition on the flow behaviour of the system.…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, considerable theoretical and experimental studies have been carried out using two different approaches: synthetic emulsions measured in a rheometer [3][4][5][6][7] and emulsions induced in pipe flow. [8][9][10][11][12][13][14][15] However, a few works have been carried out by simultaneously using two systems. [16][17][18][19] Masalova et al [16] studied the rheological and transport properties of water-in-oil emulsions.…”
Section: Introductionmentioning
confidence: 99%